2017
DOI: 10.1111/pde.13170
|View full text |Cite
|
Sign up to set email alerts
|

Molluscum Contagiosum of the Gluteal Cleft: Observations and Implications for Management in Five Children

Abstract: Molluscum contagiosum (MC) is a common, self-limited skin infection caused by a double-stranded DNA virus of the family Poxviridae. Although the morphology of the disease is well described, MC presenting at unusual sites can exhibit atypical morphology, resulting in misdiagnosis. This observational, retrospective case series discusses the novel morphology of MC presenting in the intergluteal cleft of five children seen in the outpatient dermatology clinic of an academic medical center. We present this case ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Of note, some patients were receiving simultaneous liquid nitrogen therapy 5 . Additionally, a case study of a 19‐month‐old patient with MC also demonstrated significant improvement to intralesional Candida antigen 8 . Lesions cleared within 3 months of the therapy without recurrence.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of note, some patients were receiving simultaneous liquid nitrogen therapy 5 . Additionally, a case study of a 19‐month‐old patient with MC also demonstrated significant improvement to intralesional Candida antigen 8 . Lesions cleared within 3 months of the therapy without recurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages with intralesional immunotherapy include prevention of recurrence and treatment of recalcitrant lesions. No recurrence was seen in all patients who completely responded to Candida, MMR vaccine, OK‐432, and vitamin D3 6‐9,11,13,14 . Intralesional PPD and interferon α may be an inferior choice in preventing recurrences 10,12 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations